A COMPARATIVE CLINICAL STUDY ON THE EFFECTIVENESS OF RASONA TAILA AND GANDHARVAHASTADI ERANDA TAILA IN GRIDHRASI (SCIATICA) - Athira.C; Ajay Bhat U (International Journal of Ayurveda and Pharma Research, 2020)
Gridhrasi is a Vyadhi characterized by Stambha (stiffness), Ruk (pain), Toda (pricking pain), Spandana (twitching) etc. Though it is of two types – Vataja and Vatakaphaja, Vata being the prime cause for this condition has to be tackled to gain relief. Gridhrasi, according to its signs and symptoms can be compared to sciatica in modern medical science which is a painful condition in which pain commences from the buttock and radiates into the lower extremity along its posterior or lateral aspect, more or less comprising of the area of distribution of the sciatic nerve. Thus, this study was taken up to evaluate the efficacy of Rasona taila and Gandharvahastadi eranda taila in the management of Gridhrasi (Sciatica). Methods: In the present study, 60 subjects diagnosed with Gridhrasi were randomly selected and assigned into two equal groups Group A and Group B comprising 30 subjects each. Subjects of Group A received Rasona taila 10ml orally in morning before food and subjects of Group B received Gandharvahastadi eranda taila 10 ml orally in morning before food, both for duration of 21 days. The data obtained in both the groups were recorded, tabulated and statistically analyzed using appropriate statistical methods. Results: After obtaining all the necessary data, the results were formulated by applying suitable statistical tests. Group A showed better results statistically when compared to Group B. Conclusion: Rasona taila has better effects than Gandharvahastadi eranda taila both clinically and statistically in reducing the signs and symptoms of Gridhrasi.